Предмет: Алгебра, автор: ekateruna33

 sqrt{ sqrt[3]{64} } -   frac{ sqrt[5]{96} }{ sqrt[5]{3} }
 sqrt[3]{0,04} * sqrt[3]{0,2} + sqrt[4]{ 3^{8} }
Вычислите буду благодарна

Ответы

Автор ответа: oppression
0
1) sqrt{ sqrt[3]{64} } - frac{ sqrt[5]{96} }{ sqrt[5]{3} } = sqrt{4} - frac{2 sqrt[5]{3} }{ sqrt[5]{3} } =2-2=0
2)  sqrt[3]{0,04} * sqrt[3]{0,2} + sqrt[4]{3^8} = sqrt[3]{0,008} +3^2= sqrt[3]{ frac{8}{1000} } +9= sqrt[3]{ frac{1}{125} } +9=
 frac{1}{5} +9= frac{1+45}{5} = frac{46}{5} =9 frac{1}{5} =9,2
Похожие вопросы